The Effect of Gender Diversity of the Board of Directors, Board of Commissioners, and Sharia Supervisory Board on the Financial Performance of Islamic Banks in Indonesia (2018-2024) - Kintan Adrilia Salsabilla; Mohamad Irsyad (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
The rapid growth of Islamic banking in Indonesia has heightened the importance of sound corporate governance, including gender-inclusive leadership structures. Growing scholarly interest surrounds gender diversity in corporate governance as a factor capable of influencing both strategic direction and financial outcomes, although evidence from the Islamic banking sector has remained scarce and inconclusive. The present study seeks to determine how the representation of women across the board of directors, the board of commissioners, and the Sharia Supervisory Board relates to the financial performance of Indonesian Islamic banks over the years 2018 through 2024. In this study, financial performance is assessed by means of the Return on Assets (ROA) proxy. A quantitative approach was adopted, drawing on panel data sourced from 9 Islamic banks designated through a purposive sampling mechanism. Research data were gathered from the Financial Services Authority (OJK) as well as the official websites of each bank included in the sample. Partial test results indicate that gender diversity within the board of directors, the board of commissioners, and the Sharia Supervisory Board does not yield a significant influence on financial performance. A similar pattern was also found for the CAR variable, which proved to leave no meaningful effect on financial performance. The BOPO variable, however, tells a different story, it was found to exert a significant negative influence on ROA. When all independent variables were tested together, they significantly affected financial performance, showing the value of governance assessment and identifying operational efficiency as key for Islamic banking profitability.